2006
DOI: 10.1002/cncr.22428
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor‐derived proinflammatory cytokines GM‐CSF, TNF‐α, and IL‐12 in the migration and differentiation of antigen‐presenting cells in cervical carcinoma

Abstract: BACKGROUND.Proinflammatory cytokines are important in modifying the activity, differentiation, and migration of antigen‐presenting cells and may influence the survival of cancer patients. The study assessed whether GM‐CSF, TNF‐α, and IL‐12, produced by cervical cancer cells, are important for the activity, differentiation, and migration of antigen‐presenting cells.METHODS.In 90 patients with cervical carcinoma the number of monocytes/tumor‐associated macrophages (TAM), mature dendritic cells (DC), and Langerha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…The inflammatory process and granulocytosis may be an explanation for the higher levels of G-CSF both in benign and malignant lesions of the cervix [13]. The investigations of Zijlmans et al [33] and Czygier et al [34] are in agreement with our data, and support the hypothesis that GM-CSF (among other cytokines) induces an inflammatory response which assists in tumor growth and progression.…”
Section: Discussionsupporting
confidence: 92%
“…The inflammatory process and granulocytosis may be an explanation for the higher levels of G-CSF both in benign and malignant lesions of the cervix [13]. The investigations of Zijlmans et al [33] and Czygier et al [34] are in agreement with our data, and support the hypothesis that GM-CSF (among other cytokines) induces an inflammatory response which assists in tumor growth and progression.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown the presence of GM-CSF in diverse type of tumors, including breast cancer (17,(44)(45)(46)(47). GM-CSF can function as an immune adjuvant by activating NK cells and myeloid cells (48), and is widely used in antitumor therapy (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…CD68-positive cells, CD1a (Langerhans cells)-positive intraepithelial cells or DC-LAMPpositive stromal dendritic cells were visualized as described previously. 27 …”
Section: Immunohistochemistrymentioning
confidence: 99%